Changes in health insurance status and mortality in patients with acute heart failure - Viganego, Federico; Meiselbach, Mark K.; Fradley, Michael G.; Najjar, Samer S. (American heart journal plus, 2025)
Health insurance changes (HIC) can lead to coverage gaps, alter the continuity of care, potentially affecting clinical outcomes; Heart Failure (HF) is a leading contributor to hospital readmissions in the U.S. We analyzed the relationship between HIC, readmission costs and mortality in patients with HF after a recent hospitalization. We used data from the 2019 National Readmission Database to analyze 30-day re-admission incidence, costs and mortality in hospitalized HF patients in relation to HIC. Among 569,714 acute HF admissions, 4.2 % of patients (n = 4811) experienced HIC within 30 days; HIC were associated with younger age, more comorbidities, and Medicaid coverage. HIC were associated with higher readmission mortality, longer hospitalizations and increased hospital costs. HIC in high-risk HF patients are associated with worse clinical outcomes and higher cost burden, highlighting the need for efforts aimed at preserving continuity of coverage in this population.